2014
DOI: 10.1364/ao.53.00h140
|View full text |Cite
|
Sign up to set email alerts
|

Design of a free-form lens for LED light with high efficiency and uniform illumination

Abstract: A free-form secondary lens is proposed to optimize an LED light. Based on Snell's law, energy conservation law, and a Monte Carlo ray-tracing algorithm, the surface contour of the free-form lens can be determined according to the requirements of an LED light. Optical experimental results show that an optical efficiency of 95.69% can be achieved by the lens, of which the illumination uniformity 0.317 is higher than the commercial illumination uniformity 0.259. The lens does not need the help of a white ring hol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In order to construct a new LED CBL tunnel light, a free surfaced secondary lens was designed and produced to tailor the light of a 50 W white-light LED array. The lens uses the internal reflection and refraction of light to work, which is different from traditional optical LED devices, such as optical reflectors or total internal reflection (TIR) devices [9,18]. Through optical simulation experiments in a trial tunnel in Taiwan, the LED light was demonstrated to be suitable for use as a Counter Beam Light (CBL) and able to meet the CIE 88:2004 regulations for tunnel lighting with appropriate light arrangements [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…In order to construct a new LED CBL tunnel light, a free surfaced secondary lens was designed and produced to tailor the light of a 50 W white-light LED array. The lens uses the internal reflection and refraction of light to work, which is different from traditional optical LED devices, such as optical reflectors or total internal reflection (TIR) devices [9,18]. Through optical simulation experiments in a trial tunnel in Taiwan, the LED light was demonstrated to be suitable for use as a Counter Beam Light (CBL) and able to meet the CIE 88:2004 regulations for tunnel lighting with appropriate light arrangements [19][20][21].…”
Section: Introductionmentioning
confidence: 99%